Characterizing the Microstructure of Inconel 718 Powder Using X-Ray Diffractometry - Azersky, Colby J. (Tufts Archival Research Center, 2019)
This work aims to develop techniques that allow us to investigate how the degree of undercooling during the solidification process influences defect structures within the crystalline lattice of atoms. Understanding the mechanisms that drive solidification is vital to predicting and achieving desired properties of metal parts. Inconel 718 superalloy powder from the additive manufacturing facility at NASA MSFC was used as a model material for this research. To quantify defect structures, the dislocation density was estimated using the results from powder x-ray diffractometry.